ANALYSIS FEASIBILITY OF DAIRY BUFFALO MILK BUSINESS SYARIAH IN LUBUK PAKAM DISTRICT, DELI SERDANG REGENCY - Putra, Yudha Andriansyah; Harahap, Mailina; Siregar, Gustina; Sitorus, Yuda (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine and analyze the feasibility of a dairy buffalo business in syariah system in Lubuk Pakam District, Deli Serdang Regency.This research was conducted in Lubuk Pakam District, Deli Serdang Regency. This study used a saturated or census sampling method. In this study, the respondents were 7 dairy buffalo milk farmers in Lubuk Pakam District. Data analysis uses BEP (Break Event Point) and R/C ratio (Return Cost Ratio). The results of the feasible to cultivate because it had obtained the R/C ratio (Revenue Cost Ratio) is 2.51 1 and the total production (